Cytokine‐induced interleukin‐1 receptor antagonist protein expression in genetically engineered equine mesenchymal stem cells for osteoarthritis treatment. (22nd April 2018) - Gabner, Simone; Ertl, Reinhard; Velde, Karsten; Renner, Matthias; Jenner, Florien; Egerbacher, Monika; Hlavaty, Juraj
Abstract: Background: A combination of tissue engineering methods employing mesenchymal stem cells (MSCs) together with gene transfer takes advantage of innovative strategies and highlights a new approach for targeting osteoarthritis (OA) and other cartilage defects. Furthermore, the development of systems allowing tunable transgene expression as regulated by natural disease‐induced substances is highly desirable. Methods: Bone marrow‐derived equine MSCs were transduced with a lentiviral vector expressing interleukin‐1 receptor antagonist (IL‐1Ra) gene under the control of an inducible nuclear factor‐kappa B‐responsive promoter and IL‐1Ra production upon pro‐inflammatory cytokine stimulation [tumor necrosis factor (TNF)α, interleukin (IL)‐1β] was analysed. To assess the biological activity of the IL‐1Ra protein that was produced and the therapeutic effect of IL‐1Ra‐expressing MSCs (MSC/IL‐1Ra), cytokine‐based two‐ and three‐dimensional in vitro models of osteoarthritis using equine chondrocytes were established and quantitative real‐time polymerase chain reaction (PCR) analysis was used to measure the gene expression of aggrecan, collagen IIA1, interleukin‐1β, interleukin‐6, interleukin‐8, matrix metalloproteinase‐1 and matrix metalloproteinase‐13. Results: A dose‐dependent increase in IL‐1Ra expression was found in MSC/IL‐1Ra cells upon TNFα administration, whereas stimulation using IL‐1β did not lead to IL‐1Ra production above the basal level observed in nonstimulated cells as a result of the existing feedback loop. Repeated cycles of induction allowed on/off modulation of transgene expression. In vitro analyses revealed that IL‐1Ra protein present in the conditioned medium from MSC/IL‐1Ra cells blocks OA onset in cytokine‐treated equine chondrocytes and co‐cultivation of MSC/IL‐1Ra cells with osteoarthritic spheroids alleviates the severity of the osteoarthritic changes. Conclusions: Thus, pro‐inflammatory cytokine induced IL‐1Ra protein expression from genetically modified MSCs might represent a promising strategy for osteoarthritis treatment.